PENETRASI ISLAM PURITAN DI PEDESAAN: Kajian tentang Pola Kepengikutan Warga Majlis Tafsir Al-Quran - Jinan, Mutohharun (Muhammadiyah University Press, 2013)
This paper discusses about the expansion of the MTA, as a puritan movement,in the countryside, with a sociological approach and a theory about the characteristicsof the purification. MTA is a purification movement, based on the Jamaâah and Imamateteachings. The implementation of the Imamate doctrine makes all followers of thepeasants, workers, and employees very obedient to a single leader. Their following iscaused by internal and external factors. The internal factors include the expertise of themissionary actors in dialogic preaching, the application of Imamate teaching, and socialsolidarity and brotherhood among the followers. The external factors included the moreopening chances for the Islamic missionary movements as the implications ofdemocratization. The relationship pattern between the elite and the followers is moreinfluenced by the charisma of the leader or authority positioned as an Imam to befollowed. The most prominent follower development pattern is that of sermons, whichcover general, branch, group (usrah), and special group sermons.Key words: Islamic puritanism, rural areas, Majlis Tafsir Al-Quran (MTA)Makalah ini membahas perkembangan Majlis Tafsir Al-Quran (MTA)sebagaigerakan puritan di pedesaan, dengan pendekatan sosiologis dan teori tentangkarakteristik gerakan purifikasi. MTA merupakan gerakan purifikasi yang berbasispada ajaran jamaah dan imamah. Pengikut dari kalangan petani, buruh, dan pegawaisangat taat kepada pemimpin tunggal. Kepengikutan mereka disebabkan faktor internaldan eksternal. Faktor internal meliputi kepiawaian aktor dalam berdakwah secaradialogis, penerapan ajaran imamah, dan ukhuwah atau solidaritas sosial antarpengikut.Faktor eksternal meliputi semakin terbukanya gerakan dakwah Islam sebagai implikasidari demokratisasi. Pola hubungan pengikut dan elite lebih dipengaruhi oleh kharismaatau kewibawaan pemimpin diposisikan sebagai imam yang wajib diikuti. Polapembinaan warga yang paling utama adalah melalui pengajian, yaitu pengajian umum,pengajian cabang, pengajian kelompok (usrah), pengajian gelombang khususi.Kata kunci: Islam puritan, pedesaan, Majlis Tafsir Al-Quran